Suppression of IL-6 mediated NFκB signaling pathway as possible osteoprotective mechanism of Millettia aboensis - Amara A. Ajaghaku; Daniel L. Ajaghaku; Felix A. Onyegbule; Festus Basden C. Okoye (Elsevier, 2021)
Despite the long standing traditional use of Millettia aboensis in the management of menopausal symptoms and diseases including osteoporosis, no scientific evidence has been reported on their osteoprotective effect. This study investigated the osteoprotective effect of phytoestrogen rich fraction (PERF) of M. aboensis root extract. Osteoporosis was induced by surgical removal of the ovaries to mimic menopause associated disease condition. The animals were treated separately with 200 and 400 mg/kg of the PERF daily for 30 days. Bone resorption marker - acid phosphatase, bone formation marker - alkaline phosphatase and bone minerals - calcium and phosphorous were used to monitor the effect of the PERF on bone turnover while the effect on osteoporosis associated cytokines - IL-6 and the transcription factor, NFκB were used to determine possible mechanism of action. Phytoestrogen composition of the PERF was determined as 9α-hydroxypinoresinol, genistein 6C glucoside, isoprunetin 8C glucose, daidzein, and neobavaisoflavone by dereplication using HPLC-DAD-MS analysis. Ovariectomy-induced increase in bone resorption marker, ACP (1.94±0.17 IU/L) as well as the compensatory increase in bone formation marker, ALP (94.63±0.91 IU/L) were significantly (P<0.05) suppressed by 200 mg/kg of PERF (1.5 ± 0.03 and 60.79±0.78 IU/L respectively). Treatment with the PERF at 400 mg/kg also improved bone mineral density as demonstrated by significant (p<0.05) increase in calcium level from 6.62±0.13 to 8.25±0.15 mg/dl and non-significant (p>0.05) increase in serum phosphorous concentration in the treated animals from 4.08±0.40 to 5.53±0.16 mg/dl. Significant (p<0.05) surge of NFκB (5.21 ng/mL) and IL-6 (238.67 pg/ml) were recorded in the OVX controls compared to the sham-operated control with values 2.28 ng/mL and 85.67 pg/mL respectively. Administration of PERF at 400 mg/kg significantly (p<0.05) reduced the levels of NFκB to 2.07 ng/mL and IL-6 to 131.42 pg/mL. Our findings showed that PERF of M. aboensis extract has osteoprotective effect and that inhibition of IL-6 and NFκB may be responsible for this pharmacological activity.